If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 = 3x Solving 19 = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 19 + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 19 + -3x = 0 Add '-19' to each side of the equation. 19 + -19 + -3x = 0 + -19 Combine like terms: 19 + -19 = 0 0 + -3x = 0 + -19 -3x = 0 + -19 Combine like terms: 0 + -19 = -19 -3x = -19 Divide each side by '-3'. x = 6.333333333 Simplifying x = 6.333333333
| X(4X+5)-3=0 | | X(4X+5)-3=5 | | 4(-4t^2+27-45)=0 | | 5x-3=-1 | | 9x^2+60x+100=0 | | 6(3-a)+7(3a+2)-4(a+5)= | | 9x-5x+8x-6x= | | (2+y)+y=4 | | 15-13x-20x^2=0 | | -X+2y=1 | | 5+(2-3)-(6-4)+7= | | 2x-10=48 | | 14+(-3)-(-6)+8= | | 7(2)+7y=-10 | | 72+7y=-10 | | X+(2+X)=4 | | 54+68=158 | | 6(k-2)-7=3k-(2k-3) | | 6w^2-4w^3= | | 1/2(6x+4)=x+2(x+1) | | 2(x+1)=8-x | | 4a-5=2(a+1)+9a+2 | | x-6=2(x-5)-6(x-4) | | 21.00+0.50x-0.50x=1.50x-0.50x | | 4y=-40 | | x^2+50x+47=0 | | 8m+4-2m=m+1 | | 5(x+1)-3=2x-1 | | 2r^3-14r+12=0 | | (7-6.35)/6.5+9.9= | | t=ub^2 | | x+9=2(x+7) |